2D ZIF-L(Zn) for Hybrid Copolymerization of Methyl Methacrylate and ε-Caprolactone under Solvent-free Medium (Journal of Scientific Research, 2024)
Herein, we report the hybrid copolymerization of methyl methacrylate (MMA) and ε-caprolactone (CL). 2D metal-organic frameworks, ZIF-L as a robust polymerization catalyst, can catalyze this hybrid copolymerization. Though these monomers differ from each other in structure and activity, different characterization techniques (1H-NMR, 13C-NMR, GPC, DSC, fractional precipitation techniques) confirm that they form biodegradable block copolymer PMMA-b-PCL with high molecular weight (1190 kg/mol). Also, PXRD and SEM results of the recovered ZIF-L reveal that the catalyst ZIF-L is remarkably stable even after a long-time polymerization reaction with no significant loss in activity.